Alternative and sustainable method for performing Gram and Wirtz-Conklin bacterial staining: Environmental and economic relevance in practical microbiology teaching (Research, Society and Development, 2021)
Stained preparations are the most commonly microscopic exam used in microbiology, as they provide a better view of microorganisms. Bearing in mind that Gram and Wirtz-Conklin staining techniques are commonly used in the routine of microbiology laboratories and in practical classes, this project aimed to compare the standard staining technique on slide surfaces, with the technique by immersion, which in turn can avoid waste of dyes, environmental impact and reduce laboratory and teaching costs. Thus, bacterial smears (Escherichia coli; Staphylococcus aureus; Alicyclobacillus acidoterrestris and Bacillus subtilis) were made on glass slides, followed by flame fixation. After, the slides were submitted to staining using the surface technique and the immersion technique. Subsequently, the slides were viewed under a standard optical microscope and the resolution of the images and tinting characteristics were evaluated and recorded. The staining by immersion, both for Gram stain and Wirtz-Conklin, avoided the waste of the dyes used in the techniques, as well as, the saturation of the solutions after many slide passes. Thus, the immersion staining technique is favorable for use in classes or microbiology laboratories. The application of this technique has shown significant results for the reduction of waste and, consequently, the impacts on the environment and the economy of educational institutions.